2018
DOI: 10.1111/appy.12339
|View full text |Cite
|
Sign up to set email alerts
|

The influence of resilience and coping strategies on suicidal ideation among Chinese undergraduate freshmen in Hong Kong

Abstract: Introduction The purpose of this study was to examine the relationship between resilience and suicidal ideation, with coping strategies regarded as a mediator. Methods A total of 422 Hong Kong undergraduate students were recruited with convenience sampling. Results Simple linear regression was used to verify the negative relationship between resilience and suicidal ideation (P < 0.001). The results revealed that two out of four tested mediation models were accepted, with the coping strategies of approach and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
1
8
2
1
Order By: Relevance
“…Previous studies have indicated that depression is a strong predictor of suicidality [27][28][29]. In this study, a relatively small proportion of women reported suicidal ideation (2.5%), plan (0.38%) or attempt (0.47%) but the rate was substantially higher than those of other studies.…”
Section: Discussioncontrasting
confidence: 67%
“…Previous studies have indicated that depression is a strong predictor of suicidality [27][28][29]. In this study, a relatively small proportion of women reported suicidal ideation (2.5%), plan (0.38%) or attempt (0.47%) but the rate was substantially higher than those of other studies.…”
Section: Discussioncontrasting
confidence: 67%
“…Previous studies have indicated that depression is a strong predictor of suicidality (30)(31)(32). In this study, a relatively small proportion of women reported suicidal ideation (2.5%), plan (0.38%) or attempt (0.47%) but the rate was substantially higher than those of other studies.…”
Section: Discussioncontrasting
confidence: 67%
“…To assess suicide risk in adolescents, we used two different measures (i.e., depression and suicidal ideation) given the association between these variables [59,60,61]:…”
Section: Methodsmentioning
confidence: 99%